Corporate sustainable business practices and talent attraction. Issue 4 (7th November 2016) - Magbool, Mohamad Abu Huzaifah bin; Amran, Azlan; Nejati, Mehran; Jayaraman, Krishnaswamy
Abstract : Purpose: This study aims to investigate whether organizations can leverage on their sustainable business practices to attract valuable talents to gain competitive advantage over their competitors. Design/methodology/approach: Using factorial design, the authors conducted an experiment to assess the attractiveness of an organization in line with the social identity theory, based on the Bursa Malaysia corporate social responsibility (CSR) framework attributes (including environmental performance, community relation, workplace and marketplace performance). Findings: The findings of the current study supported the notion of social identity theory, as study subjects were attracted more to organizations with high corporate sustainable business (CSB) practices than organizations with low CSB practices. Specifically, findings of the current study revealed that job applicants have a higher intention to join and willingness to accept a job offer from organizations with more sustainable business practices. Research limitations/implications: This study is limited by its sample size and selection, self-reported measures and its cross-sectional nature. Practical implications: Understanding the most preferred attribute of CSB practices will enable organizations to focus their valuable resources rightfully to market their CSR efforts for obtaining higher organizational attractiveness and competitive advantage. Social implications: As many organizations perceive sustainable outcomes to be costly, demonstrating the positive link between CSB practices and organizational attractiveness for talents warrants a win-win paradigm. Originality/value: Talented workforce is essential for differentiating an organization from its competitors. As human resources are mostly unique and non-imitable, it has been recommended as a newly minted strategy to enable organization to achieve sustainable competitive advantages.